Analysis of the Tenth Grade Students’ Numeracy Literacy Ability in Solving Contextual-Based Story Problems - Arumsari, Diny; Firmansah, Fery; Sungkono, Joko; Wijayanti, Septiana; Tasari, Tasari (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
The aim of this study was to describe the tenth grade students’ numeracy literacy ability in solving contextual-based story problems at SMK Negeri 4 Klaten in the 2022/2023 academic year. Taking research subjects using purposive sampling technique. The data collection techniques are documentation, tests and interviews. Based on the results of the study, it was obtained: students' numeracy literacy ability in identifying and understanding problems for students in the upper group had very good criteria (100%), students in the middle group had less criteria (50%) and students in the lower group had very poor criteria (0%); students' numeracy literacy ability in understanding and using symbols and numbers for group students with very good criteria (91.7%), middle and lower group students with very good criteria (87.5%); students' numeracy literacy ability in selecting and applying problem solving methods for students in the upper group had very good criteria (87.5%), students in the middle group had good criteria (79.2%), students in the lower group had good criteria (70.8%); as well as the ability of students' numeracy literacy in drawing and explaining the conclusions of the final results obtained from solving problems for students in the top group with very good criteria (91.7%), students in the middle and lower groups with good criteria (66.7%). In solving contextual-based word problems, students made several mistakes due to students' lack of accuracy and thoroughness both in reading the questions, writing answers and the calculation process.